PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL - Darmawan, Akhmad; Putragita, Yudhistira; Purnadi, Purnadi; Aryoko, Yudistira Pradipta; sunardi, sunardi (Universitas Muhammadiyah Palembang, 2020)
The research aims to examine the effect of profitability and leverage on firm value with Corporate Social Responsibility as a moderating variable and company size as a control variable. The subject of this research uses manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016-2018. Data collection techniques used in this study were purposive sampling and with a sample size of 107 samples. While the data analysis techniques used in this study is classic multiple regression analysis with absolute. The analysis shows that profitability has a positive and significant effect on firm value, while leverage has a negative and significant effect on firm value, and Corporate Social Responsibility is able to moderate, then firm size has a significant positive effect on firm value